Controversies in the Management of Lateral Pelvic Lymph Nodes in Patients With Advanced Rectal Cancer: East or West? - Otero de Pablos, Jaime; Mayol, Julio (Frontiers in Surgery, 2020)
The presence of lateral pelvic lymph nodes ( LPLN ) in advanced rectal cancer entails challenges with ongoing debate regarding the role of prophylactic dissection versus neoadjuvant radiation treatment. This article highlights the most recent data of both approaches: bilateral LPLN dissection in every patient with low rectal cancer (Rb) as per the Japanese guidelines, versus the developing approach of neoadjuvant radiotherapy as per Eastern countries. In addition, we also accentuate the importance of a combined approach published by Sammour et al where a simple “one-size-fits-all” strategy should be abandoned. Rectal cancer treatment is well established in Western countries. Patients with advanced rectal cancer will undergo radiation +/- chemo neoadjuvant therapy followed by TME. In the Dutch TME trial, TME plus radiotherapy showed that the presacral area was the mos frequent site of recurrence and not the lateral pelvic wall. Supporting this data, the Swedish study also concluded that LPLN metasastais is not an important cause of local recurrence in patients with low rectal cancer. Therefore, Western approach is CRM-orientated and prophylactic LPLN dissection is not performed rountinely as the NCCN guideline does not recommend its surgical removal unless metastases are clinically suspicious. The paradigm in Eastern countries differs somewhat. The Korean study demonstrated that adjuvant radiotherapy without lateral lymph node dissection was not enough to control local recurrence and LPLN metastases. The Japanese Trial JCOG 0212 demonstrated the effects of LPLN dissection in reducing local recurrence in the lateral pelvic compartiment. We agree with Sammour and Chang on the fact that rather than a mutual exclusivity approach, we should claim for an approach where all available modalities are considered and used to optimize treatment outcomes, classifying patients into 3 categories of LPLN: low risk ( cT1/T2/earlyT3 (and Ra) with clinically negative LPLN on MRI; Moderate risk ( cT3+/T4 with negative LPLN on MRI) and high risk ( clinically abnormal LPLN on MRI ) Treatment modality should be based on detailed pretreatment workup and an individualized approach that considers all options to optimize the treatment of patients with rectal cancer in the West or the East.